A survey study of Chinese adolescents’ mental and interpersonal quality: Evidence from COVID-19 pandemic - Huang, Leping; Zhu, Yingfu; Kang, Wei; Zhu, Chunmu (Frontiers in Psychology, 2022)
Since 2019, the COVID-19 pandemic, as a global public health emergency, has led to stringency measures (such as lockdown) of various degrees worldwide. As these measures such as social distancing measures and mandatory lockdown are intended to minimize social mobility, they have exerted remarkable impact on individuals’ mental health, particularly, adolescents and children. The mental health problems caused include fear, anxiety, sense of isolation and development of more maladaptive behaviors due to prolonged lockdown and restricted interpersonal contact. However, well adaption status and stable interpersonal relationships play an important role in maintaining and promoting the mental health of adolescents and children. This study aims to gain a new sight of understanding of the mental health quality of Chinese adolescents during the COVID-19 Pandemic in terms of adaptation and interpersonal quality. The study is based on a survey on a total of 7,318 junior and senior high school students aged 12–18 years in various regions of China, and intended to examine the differences in adolescent mental health quality by sociodemographic variables such as gender, grade, urban and rural areas, only child, and parental education level. Our study finds that Chinese adolescents show an overall good adaptation and interpersonal quality during the lockdown. However there exists disparity across different categories in developmental patterns of adaptation and interpersonal quality. In addition, good family environment, moderate financial and emotional support, higher parental education level, etc. contribute to the cultivation and improvement of adolescents’ mental health quality. Finally, we suggest that the government and researchers should pay more attention to adolescents’ mental health issues in terms of adaption status and interpersonal relationships during the COVID-19 pandemic, especially for disadvantaged social groups such as girls, younger students, and low-income family students.